Exploring the Voice of Voiceless Groups in Lamsal’s Epic Agni [Fire] - Rai, Man Kumar (JODEM: Journal of Language and Literature, 2024)
This article studies identity crisis and suppressed voice of Dalit community depicted in Nawaraj Lamsal’s epic Agni. The epic tries to raise unheard voice of voiceless groups like Thule Kami and his community. The study introduces the sacrifices of Dalit community in nation building through the creation of various tools for farmers and weapons for warriors. Through his work, he questions the government and ruling class people about sanctioning of human rights to dalits, indeginous people and women. Lamsal’s epic narrates the story of Thule and Thule’s community in order to make people know about the sacrifice of such othered people in leading society ahead. Moreover, caste system has left a pervasive mark on nearly every aspect of Nepali society. In caste based society, untouchable communities are born into a lifetime of marginalization, exclusion, and human rights violation. For the analysis of the characters and voiceless voice, subaltern studies and idea of Gayatri Spivak regarding unheard voice of marginalized people have been used. Spivak argues that subaltern can not represent themselves, they need to be represented. The intellectuals, historians or politicians often give more focus to their individual interest rather than the stories of subaltern groups